The reaction of consumer spending and debt to tax rebates: Evidence from consumer credit data - Sumit Agarwal; Chunlin Liu; Nicholas S. Souleles (Federal Reserve Bank of Chicago, 2007)
We use a new panel dataset of credit card accounts to analyze how consumers responded to the 2001 federal income tax rebates. We estimate the monthly response of credit card payments, spending, and debt, exploiting the unique, randomized timing of the rebate disbursement. We find that on average consumers initially saved some of the rebate, by increasing their credit card payments and thereby paying down debt. But soon afterwards spending increased, counter to the canonical Permanent-Income model. For people whose most intensively used credit card account is in the sample, spending on that account rose by over 200 cumulatively over the nine months after rebate receipt, which represents over 40% of the average household rebate. Because these results relied exclusively on exogenous, randomized variation, they represent compelling evidence of a causal link from the rebate to spending. Further, we found significant heterogeneity in the response to the rebate across different types of consumers. Notably, spending rose most for consumers who were initially most likely to be liquidity constrained according to various criteria, for example consumers who appeared to be initially constrained by their credit limits (before making additional payments). By contrast, debt declined most (so saving rose most) for unconstrained consumers. These results suggest that liquidity constraints are important. More generally, we found that there can be important dynamics in consumers' response to 'lumpy' increases in income like tax rebates, working in part through balance sheet (liquidity) mechanisms.
Keywords: D91; E21; E51; E62; G2; H31; 330; consumption; saving; life-cycle model; Permanent-Income Hypothesis; liquidity constraints; fiscal policy; tax cuts; tax rebates; windfalls; credit cards; consumer credit; consumer balance sheets; household finance; Steuerbegünstigung; Einkommensteuer; Verbraucherausgaben; Private Verschuldung; Kreditkarte; USA